Contemporary World Migration - Mesić, Milan, sociolog (2008)
International migration has risen to the top of the global policy agenda. International (global) migration has expended in terms of scale, scope and complexity, and the states (as still the most relevant players in the international relations), and other stakeholders have become more and more aware that international migration has challenged contemporary societies (and global world) in many important respects. The most fundamental question is posed before the major stakeholders here – how to realize in the most effective ways economic, social and cultural benefits of international migration, and on the other hand how to minimize or at least effectively control various negative aspects and consequences of it (first of all illegal cross-boarder movements, primarily human trafficking and migrant smuggling)
Projekt MZOS
ENG